The Encyclopedic Palace : Short Guide for the 55th International Art Exhibition la Biennale di Venezia. - Gioni, Massimiliano; Tenconi, Roberta; Bell, Natalie; Biennale di Venezia Venice 2013 (Venice : Marsilio Editori, 2013)
Van Lieshout, Erik ; Kratansson, Ragnar ; Bock, John ; Donnely, Trisha ; Khalili, Bouchra ; Nazareth, Paulo ; Ortega, Damian ; Paolini, Marco ; Steyerl, Hito ; Van Caeckenbergh, Patrick ; Schmidt, Michael ; Althamer, Pawel ; et al.
55.th International Art Exhibition, la Biennale di Venezia, Venice, June 1 - November 24, 2013
kunstcatalogus